Intensive Care Ethics in Evolution - Hall, Katherine (Bioethics, 1997)
The ethics of treating the seriously and critically ill have not been static throughout the ages. Twentieth century medicine has inherited from the nineteenth century a science which places an inappropriate weight on diagnosis over prognosis and management, combined with a seventeenth century duty to prolong life. However other earlier ethical traditions, both Hippocratic and Christian, respected both the limitations of medicine and emphasised the importance of prognosis. This paper outlines some of the historical precedents for the treatment of the critically ill, and also how the current paradigm limits clinical practice and causes ethical tensions. An understanding that other paradigms have been ethically acceptable in the past allows wider consideration and acceptance of alternatives for the future. However future alternatives will also have to address the role of technology, given its importance in this area of medicine.